Development of a Protocol for In- vitro Establishment of Gyrinops walla - Selvaskanthan, S.; Pushpakumara, D.K.N.G.; Eeswara, J.P. (Tropical Agricultural Research, 2018)
Gyrinops walla is a fragrance-producing resinous tree growing in the natural forests of Sri Lanka. There has been a very high demand for G. walla, resulting over exploitation of the species. Tissue culture techniques can be used to conserve this species and to produce bioactive secondary metabolites responsible for the fragrance. The establishment of the aseptic culture is considered as the critical stage of in-vitro culture. The present study was carried out to develop a protocol for the establishment of in vitro cultures of G. walla using the explants of leaf, shoot tips and axillary buds. Among the treatments, the best results in producing uncontaminated, green and alive cultures were obtained when the explants of shoot tips and leaves (80% and 100%, respectively) were treated with 10% (v/v) of bleach (NaOCl) solution with two drops of tween-20. Immature axillary buds from the 3rd to 5th nodes from shoot tips produced the best explant in producing the aseptic culture. Surface sterilization with 10% (v/v) bleach coupled with 0.2% of HgCl2 for 5 min reduced the percentage of contaminated cultures by 20% and improved the percentage of uncontaminated green and live cultures of axillary bud to 73%.
Keywords: Aseptic in- vitro culture; Contamination; Gyrinops walla